Optimization of Treatment Methods for Purulent-Destructive Soft Tissue Diseases through the use of Laser Treatment Methods (Global Journal of Medical Research, 2022)
Purpose: Optimization of methods for the treatment of purulent-destructive diseases through the complex application of photodynamic therapy (PDT) and CO2 laser. Materials and Methods: 360 patients with purulent-destructive soft tissue disease were examined and treated. Depending on the treatment carried out, the patients were conditionally divided into 3 groups: the 1st (control group) included 118 patients who underwent conventional traditional methods of treatment; in the 2nd group (main group I) there were 120 patients who, in combination with traditional methods of treatment, used PDT with a photosensitizer (PS) 0.05% methylene blue buffer solution (MB); and the 3rd group (main group II) included 122 patients where PDT was used in combination with traditional methods of treatment (0.05% methylene blue buffer solution was used as PS) and a CO2 laser.
Keywords: photodynamic therapy; photosensitizer; methylene blue; #x421; #x41E; 2 laser; laser surgery; microbe; planimetry